RETHINKING HEIDEGGER'S DWELLING THROUGH ARABIC LINGUISTICS - El Moussaoui, Mustapha Hashem (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2020)
Inhabiting a space or dwelling has been a debatable terminology in architectural theory practice. Martin Heidegger's conference paper